Open reduction and internal fixation of purely ligamentous lisfranc injury in a rugby player: a case report - Tarmalinggam, Shangeetha; Jaapar, Mohd Shahril; Alias, Azammuddin; Abdul Kahar, Johan (Lycia Press London UK, 2023)
Objective: Lisfranc injuries are found in various injury patterns, especially in athletes. These injuries are the second most common type of foot injuries in athletes. However, the treatment decision differs and is essential in athletes for a good outcome. The main controversies in surgical management include whether to execute open or close reduction, fixation technique, and arthrodesis’ role in athletes. Case Report: A previously healthy 21 Years Old Malay gentleman sustained a sports injury diagnosed with pure ligamentous Lisfranc injury with an incomplete, partial lateral dislocation. The patient was treated with Open Reduction and Internal Fixation (ORIF) using a dorsal bridge Lisfranc locking plate. Conclusion: Early diagnosis and appropriate treatment are crucial to achieving stability in unstable Lisfranc injuries. Anatomical reduction and Lisfranc joint restoration are the keys to a good outcome. Open reduction and internal fixation are preferred methods where most athletes can return to their previous level of sports